Peran Filsafat Pendidikan Kristen Dalam Meningkatkan Pemahaman Iman Peserta Didik - Jonius Halawa; Ayunike Waoma; Mozes Lawalata (Publisher STPKat, 2024)
The purpose of this study is to explore how philosophical approaches to education rooted in Christian principles play a role in increasing students' understanding of faith. The research method applied is a qualitative study that uses a case study approach. As a framework with detailed and detailed data collection. The findings of this study suggest that consistent use of the principles of Christian educational philosophy can increase students' understanding of faith. The consequences arising from the results of this study broaden our understanding of the impact and relevance of these findings in a variety of contexts, as well as highlighting practical implications that can be used in various fields and situations and highlighting the significance of incorporating Christian values in modern educational contexts as an effort to strengthen the foundations of faith of learners.